Problem Solving and Decision Making in Educational Context - Hadi , Muhammad Zaki Pahrul; Hartono, Rudi; Rozi , Fahrur (CV Insan Kreasi Media, 2024)
Problem-solving and decision-making are crucial competencies in the educational setting, indispensable for tackling the multitude of difficulties that educators and administrators encounter on a daily basis. This paper describes the theoretical foundations and real-world uses of these processes in educational environments. The article emphasises the significance of utilising the IDEAL model (Identify, Define, Explore, Anticipate, and Look Back) proposed by Wehmeyer as a problem-solving framework. Using library research, researchers gather, analyse, and arrange data from journals, books, and past studies on the adoption of management methods in the field of education, especially in problem solving and decision-making. This paper highlights the significant influence of organised problem-solving and strategic decision-making on educational outcomes, emphasising their crucial role in promoting a flexible and flourishing educational environment.